Modern issues of performance of integrated industrial company ("Journal "U". Economy. Management. Finance.", 2022)
The article studies modern trends of performance of integrated industrial companies in Russia and in foreign countries, the role of large companies in economic development, the value of integration including intensification of various forms of industrial management while integrated industrial companies (IIC) are established and perform. IIC are of key importance when digital technologies are introduced during economic crisis and pandemic disease. The paper analyses current state of IIC in Russia in comparison with foreign companies. The main problems of performance of IIC in Russia are defined.
Keywords: integrated industrial companies; economic crisis; innovation activity; forms of industrial management; capital concentration